Hubungan Kematangan Emosi dengan Perilaku Agresif pada Siswa SMK - Taufik, Rifki (Jurnal Empati Bimbingan dan Konseling, 2024)
This study aims to determine the relationship between emotional maturity and aggressive behavior in vocational students. This research was conducted on SMK class X students. The sample in this study amounted to 135 students with probability sampling techniques. The type of research used in this study is quantitative research. The measurement tool used for data collection uses the emotional maturity scale and the aggressive behavior scale. Statistical data analysis using Pearson product moment analysis test with the help of SPSS statistics version 26. The correlation coefficient obtained is -0.426 with a significance value of 0.000 (p0.05). These results show that the hypothesis proposed by the researcher is accepted. And the value of the negative correlation coefficient shows that the direction of the relationship between the two variables is negative, meaning that the higher the emotional maturity, the lower the aggressive behavior.